Using Evidence-Based Teaching Activities Integrated with the Storyline Approach in the Social Studies Courses - (:unkn) unknown (HACETTEPE UNIV, 2018)
It is aimed to provide knowledge skills of social scientists to the students by suggesting them the use of evidence in the learning activities in various sections of the social studies course curriculum. In this respect, it is necessary to demonstrate the effectiveness and functionality of evidence-based teaching activities at primary school level. It was also worth investigating the effectiveness of unifying the Storyline approach developed in Scotland at the beginning of 1980s and evidence-based teaching, in the teaching process. To this end, in this research, the effects of evidence-based teaching activities integrated with the Storyline approach on student products and the students' views on the teaching process in question were tried to be determined. In the study, data were collected from work sheets, camera records, and teacher and student diaries. As reported by the results of the research, a significant proportion of the products realized by the students are very qualified and qualified. In addition to this, students have been able to work more successfully in visual evidence-based teaching activities. It was also found that students' opinions on the evidence-based teaching process integrated with the Storyline approach were positive.
Keywords: Social Studies; Storyline Approach; Evidence-based Teaching